A Single Chiral Nanoparticle Induced Valley Polarization Enhancement. Issue 37 (13th August 2020) - Kim, Sejeong; Lim, Yae‐Chan; Kim, Ryeong Myeong; Fröch, Johannes E.; Tran, Thinh N.; Nam, Ki Tae; Aharonovich, Igor
Abstract: Valley polarization is among the most critical attributes of atomically thin materials. However, increasing contrast from monolayer transition metal dichalcogenides (TMDs) has so far been challenging. In this work, a large degree of circular polarization up to 45% from a monolayer WS2 is achieved at room temperature by using a single chiral plasmonic nanoparticle. The increased contrast is attributed to the selective enhancement of both the excitation and the emission rate having one particular handedness of the circular polarization, together with accelerated radiative recombination of valley excitons due to the Purcell effect. The experimental results are corroborated by the optical simulation using the finite‐difference time‐domain (FDTD) method. Additionally, the single chiral nanoparticle enables the observation of valley‐polarized luminescence with a linear excitation. The results provide a promising pathway to enhance valley contrast from monolayer TMDs and utilize them for nanophotonic devices. Abstract : A single chiral plasmonic nanoparticle‐induced valley polarization contrast enhancement at room temperature is demonstrated. A gold nanoparticle enhances the degree of circular polarization of a monolayer WS2 from 16% to 45%, benefited by the large chiroptical response of a chemically synthesized nanoparticle.